2020
DOI: 10.1016/j.eclinm.2020.100484
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Micro-Structural Changes in COVID-19 Patients – An MRI-based 3-month Follow-up Study

Abstract: Background Increasing evidence supported the possible neuro-invasion potential of SARS-CoV-2. However, no studies were conducted to explore the existence of the micro-structural changes in the central nervous system after infection. We aimed to identify the existence of potential brain micro-structural changes related to SARS-CoV-2. Methods In this prospective study, diffusion tensor imaging (DTI) and 3D high-resolution T1WI sequences were acquired in 60 recovered COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
551
9
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(649 citation statements)
references
References 39 publications
32
551
9
15
Order By: Relevance
“…The first hint of rSpike toxicity was the distinct swimming behavior that adult females presented after the protein injection. In fact, some recent studies have reported that the SARS-CoV-2 may affect the nervous system 2628 as the peripheral nervous system 2931 , particularly in the most severe cases of infection 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The first hint of rSpike toxicity was the distinct swimming behavior that adult females presented after the protein injection. In fact, some recent studies have reported that the SARS-CoV-2 may affect the nervous system 2628 as the peripheral nervous system 2931 , particularly in the most severe cases of infection 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of subcortical white matter is critically important for maintenance of cognitive function [71,72], and one of the consequences of white matter damage in COVID-19 is likely to be cognitive impairment. This was highlighted by the neuroradiological demonstration that damage to white matter and disruption of functional integrity in brain regions such as the hippocampus, at 3-month follow-up in recovered COVID-19 patients, was associated with memory loss [9].…”
Section: The Types Of Cerebral Ischaemic Damage Seen In Covid-19 Arementioning
confidence: 99%
“…A recent report described a 'dysexecutive syndrome consisting of inattention, disorientation, or poorly organised movements in response to command' in 33% of 43 patients discharged from hospital [7]. Moreover, neuroradiological evidence of microstructural damage and disruption of functional brain integrity at 3-month follow-up in recovered COVID-19 patients [9] indicates potential long-term neurological consequences in severely affected COVID-19 patients (reviewed [10]). Acute cerebrovascular disease (CVD), typically presenting as ischaemic stroke but occasionally as intracerebral haemorrhage (ICH), has emerged as an important clinical feature in COVID-19 (reviewed in [5]).…”
Section: Introductionmentioning
confidence: 99%
“…A recent MRI-based 3-month follow-up study demonstrates that 55% of patients who recovered from COVID-19 infection had neurological symptoms and exhibited significantly higher gray matter area in brain regions relevant to memory, smell, tremor etc. (Yiping et al, 2020). Together, these data indicate that neurological manifestations of COVID-19 are relatively frequent especially in patients with severe disease, raising questions about mechanism, chronic consequences, and management since neither a vaccine nor specific treatment is available.…”
Section: Sars-cov-2 and The Central Nervous Systemmentioning
confidence: 98%